Pengaruh Tax Minimization, Debt Covenant dan Tunneling Incentive Terhadap Transfer Pricing Pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2020-2024 - Anisa, Nur; Indriasih, Dewi; Mubarok, Abdulloh (Jambura Economic Education Journal, 2026)
The research aims to assess how tax minimization, debt covenant, and tunnelling incentives affect transfer pricing. The independent variables assessed were tax minimization, debt covenant, and tunnelling incentive, while transfer pricing functioned as dependent variables. This study examined a total of 81 companies, with samples selected using purposive sampling techniques. In the end, forty-four mining companies listed between 2020 - 2024 on the IDX became a sample. A quantitative approach was used, relying on secondary data, with data analysis applied through multiple linear regression utilizing  SPSS software. The results demonstrate that whereas tunnelling incentives have a negative impact on transfer pricing, tax minimization has a favorable effect, and debt covenants have no influence at all. These results provide important new information about the variables influencing transfer pricing strategies in the mining industry.